Complex karyotype in myelodysplastic syndromes: Diagnostic procedure and prognostic susceptibility - Mohammad Shahjahani; Elham Homaei Hadad; Shirin Azizidoost; Kowsar Chenani Nezhad; Saeid Shahrabi (Oncology Reviews, 2019)
Complex karyotype (CK) is a poor prognosis factor in hematological malignancies. Studies have shown that the presence of CK in myelodysplastic syndrome (MDS) can be associated with MDS progression to acute myeloid leukemia. The goal of this review was to examine the relationship between different types of CK with MDS, as well as its possible role in the deterioration and progression of MDS to leukemia. The content used in this paper has been obtained by a PubMed and Google Scholar search of English language papers (1975-2018) using the terms complex karyotype and myelodysplastic syndromes. A single independent abnormality can be associated with a good prognosis. However, the coexistence of a series of abnormalities can lead to CK, which is associated with the deterioration of MDS and its progression to leukemia. Therefore, CK may be referred to as a prognostic factor in MDS. The detection of independent cytogenetic disorders that altogether can result in CK could be used as a prognostic model for laboratory and clinical use.